Analisis Yuridis Pergeseran Paradigma Pemutusan Hubungan Kerja dari Unfair Dismissal ke Efisiensi Perusahaan (Perbandingan Era Ketenagakerjaan dan Era Cipta Kerja) - Muh Amin Saleh; Solikhin, Solikhin (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2026)
This study examines the paradigm shift in termination of employment from unfair dismissal to corporate efficiency by comparing Law Number 13 of 2003 concerning Manpower and Law Number 6 of 2023 concerning Job Creation. Two research questions are proposed. First, how changes in the regulation of termination of employment shape this paradigm shift. Second, how the regulation of termination of employment due to efficiency in Law Number 6 of 2023 compares with Law Number 13 of 2003 in terms of worker protection. This study uses a normative juridical method. The results show that the paradigm shift occurs in three dimensions: the basic framework (from ultimum remedium to flexibility), the efficiency position (from limited reasons with high compensation to broad reasons with lower compensation), and the logic of protection (from preventive to repressive, based on immature social security). The regulation of termination of employment due to efficiency in Law Number 6 of 2023 continues to provide protection, but qualitatively decreases due to the loss of objective parameters and the absence of preventive obligations. The proposed strengthening strategies include establishing objective efficiency parameters, strengthening oversight mechanisms, evaluating the Job Loss Guarantee program, and ensuring strict interpretation by the judiciary. This study concludes that without these improvements, the paradigm shift could potentially conflict with the principles of the rule of law and social justice.